Heart of the Matter: From Hemoptysis and Left Arm Pain to Diagnosis, Importance of Imaging - Gülhan, Didem; Çimci, Murat; Durmaz, Emine Şebnem; Kılıçkıran Avcı, Burçak (Cerrahpaşa Medical Journal, 2024)
Cite this article as: Gülhan D, Çimci M, Durmaz EŞ, Kılıçkıran Avcı B. Heart of the matter: from hemoptysis and left arm pain to diagnosis, importance of imaging. Cerrahpaşa Med J. 2024;48(3):309-310.